Studi Etnosains Transformasi Budaya Wiwitan dalam Konteks Sains Modern - Nisak, Choirun; Diyah Ayu Widyaningrum; Wijayanti, Titik; Iza, Nikmatul (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
One form of local culture that contains scientific wisdom is the wiwitan tradition related to ecology, astronomy, and natural management that is still relevant to modern scientific concepts. However, not all elements of society know about the wiwitan tradition, especially the younger generation. The wiwitan tradition, which is local wisdom, is an ancestral heritage that must be preserved, one of which is through an ethnoscience approach. The wiwitan tradition has undergone transformation along with globalization. The study of the transformation of wiwitan culture in the context of modern science has never been studied. This study aims to study the transformation of wiwitan culture in the context of modern science, using an ethnoscience approach. This study uses a qualitative descriptive method using interview techniques with farmers who have knowledge of the wiwitan tradition. Data analysis uses techniques of grouping, describing, classifying, and interpreting data. The results of the study indicate that ethnoscience studies on the wiwitan tradition are found in the types of offering plants related to biodiversity, implementation before harvest time related to the natural cycle and astronomy, values ??contained in the tradition related to sustainable agriculture. This study emphasizes the importance of integrating local knowledge in the context of modern science to maintain local wisdom and enrich science. This research is expected to continue in other ethnoscience studies of local wisdom.